Effect of Planting Media Type and Nutrient Concentration on Early Growth of Tomato (Lycopersicum Esculentum Mill) in Hydroponic System - Dwi Asmarawati (Nabatia, 2010)
The purpose of this study was to determine the effect of interaction between types of growing media with nutrient concentrations on the growth and production of tomato (Lycopersicum ecsculentum Mill) in the hydroponic system. Conducted in the plastics chamber, drum Durung Village district. Temple District. Sidoarjo. In May until September 2003. The experiment was arranged in factorial using completely randomized design (CRD) . The first factor is the concentration of nutrients, namely: control (K0), K1 = 10cc/lt of water (K1), 15cc/lt of water (K2), 20cc/lt of water (K3); the second factor is the growing media comprising: sand (M1), gravel (M2) and paddy’s husk (M3); the replay 3 times obtained 108 experimental unit. The results of the study at 45 days after planting showed: (i) the presence of interactions between the types of growing media concentration of nutrients to the number of branches as well as wet weight and root dry weight, (ii) the growing media influence the mean difference in plant height, number of branches, number of leaves, fresh weight and root dry weight, (iii) differences in nutrient concentrations perbedaan effect on the average number of branches , fresh weight and root dry weight.